Towards the edge implementation of a U-Net-based PCG segmenter - Enériz, Daniel; Rodriguez-Almeida, Antonio J.; Fabelo, Himar; Medrano, Nicolás; Calvo, Belén; Callico, Gustavo M. (Jornada de Jóvenes Investigadores del I3A, 2022)
A computer-aided cardiovascular diseases diagnostic system requires both accuracy and real-time response. This can be reached thanks to the deep model implementation on edge devices. This works introduces a reduction strategy for a heart sound segmentation model, and its impact in the implementation over low-spec FPGAs.